2016
DOI: 10.18632/oncotarget.12465
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular vesicles in mediating progression, metastasis and potential treatment of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a major cause of cancer-related death worldwide. As vectors for intercellular information exchange, the potential role of extracellular vesicles (EVs) in HCC formation, progression and therapy has been widely investigated. In this review, we explore the current status of the researches in this field. Altogether there is undeniable evidence that EVs play a crucial role in HCC development, metastasis. Moreover, EVs have shown great potential as drug delivery systems (DDSs) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 93 publications
0
68
0
Order By: Relevance
“…The exchange of exosomal packages between the cells could influence the tumor microenvironment and contribute to the tumor development [4][5][6]12]. Exosomes are easy to obtain from nearly all body fluids, including blood, urine, saliva, semen and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…The exchange of exosomal packages between the cells could influence the tumor microenvironment and contribute to the tumor development [4][5][6]12]. Exosomes are easy to obtain from nearly all body fluids, including blood, urine, saliva, semen and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to package and transfer diverse cargoes from cell to cell makes EVs important mediators of intercellular communication events that are involved in normal physiological processes, as well as in pathological conditions, such as cancer (41)(42)(43). In malignancy, EVs play a major role in cell growth, invasion, and metastasis (44,45). In the case of virus-infected cells, EVs can transfer modified protein and RNA cargo to uninfected cells, which can enhance viral pathogenesis (34,35).…”
mentioning
confidence: 99%
“…Deregulation of miRNAs has been observed in a wide range of human diseases, including HCC or other cancers . Our previous study identified several deregulated miRNAs in HCC tumor tissues (data not shown), of which miR‐199a‐5p was the most significance (Fold change: 0.0023, p <0.001).…”
Section: Introductionmentioning
confidence: 89%
“…9 Deregulation of miRNAs has been observed in a wide range of human diseases, including HCC or other cancers. [10][11][12][13][14][15] Our previous study identified several deregulated miRNAs in HCC tumor tissues (data not shown), of which miR-199a-5p was the most significance (Fold change: 0.0023, p<0.001). Although down-regulation of miR-199a-5p has been reported by others, the roles of miR-199a-5p and its novel targets are still worthy to be studied.…”
Section: Introductionmentioning
confidence: 99%